Description of the Knowledge Red Cross Youth Members about First Aid in Traffic Accidents in Pangandaran - Nuraeni, Wida; Senjaya, Sukma; Nurhamsyah, Donny (GLOBAL HEALTH SCIENCE GROUP, 2024)
The high number of deaths or disabilities due to accidents is caused by delays in handling victims and errors in providing first aid by helpers. The Youth Red Cross, as a school health cadre, has various responsibilitys, one of which is providing first aid during accidents. Objective: the study imed to determine the knowledge of youth red cross members about first aid in traffic accidents in Pangandaran. Method: This study used descriptive quantitative research methods with a cross-sectional approach. The sample of this research is all members of RCY from senior high school 1 Parigi class X and XI, totally 76 peoples. The sampling method employed was saturated sampling. The instrument used to measure knowledge of first aid in traffic accidents was developed by the researchers and validated, with all question items proving valid and reliable (Cronbach's Alpha = 0.772). Data collection was conducted using a questionnaire administered through Google Forms. The data analysis technique employed was categorical univariate analysis. Results: The results showed that 63.2% of respondents had good knowledge, 35.5% had sufficient knowledge, and only 1.3% had poor knowledge. Conclusions: These findings suggest that the knowledge levels are influenced by the training provided by the RCY coach and the availability of a guidebook on the material.